MASLAHAT DALAM HUKUMAN MATI BAGI PELAKU LGBT - Muhammad Taufan Djafri; Darussalam Syamsuddin; Abdul Syatar (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
Lesbian, Gay, Bisexual and Transgender (LGBT) is a term used since the 1990s to describe a group of people with different sexual orientations and behaviors. This term replaces the previous phrase "Gay Community". Some countries that reject LGBT people are Saudi Arabia, Yemen, Sudan and Iran, which are known to have imposed the death penalty on LGBT people. Though there have been no reports of actual death sentences in recent years. This study aims to reveal the relationship between the benefits of Islamic law and the possibility of imposing the death penalty on LGBT offenders. A normative approach is used in this study and it is found that in Islam, LGBT is prohibited. Although scholars differ on the punishment for LGBT offenders, there are still LGBT offenders found in the Muslim community. The maslahah perspective is presenting studies and guidelines that can be used as a reference in determining the appropriate punishment for LGBT offenders. The assumption about the permissibility of being LGBT can be rebutted by the presence of power that underlies one's religious beliefs. Scientists hope that punishment for LGBT offenders will not only become a discourse but should be considered if possible to be implemented. The government and all related elements must be able to provide awareness that stigma, discrimination or prejudice against LGBT people is something that can happen because religion prohibits LGBT actions and the concept of human rights is upheld in Indonesia.